2021
DOI: 10.1126/sciadv.abg5859
|View full text |Cite
|
Sign up to set email alerts
|

Piezo1 channels restrain regulatory T cells but are dispensable for effector CD4 + T cell responses

Abstract: T lymphocytes encounter complex mechanical cues during an immune response. The mechanosensitive ion channel, Piezo1, drives inflammatory responses to bacterial infections, wound healing, and cancer; however, its role in helper T cell function remains unclear. In an animal model for multiple sclerosis, experimental autoimmune encephalomyelitis (EAE), we found that mice with genetic deletion of Piezo1 in T cells showed diminished disease severity. Unexpectedly, Piezo1 was not essential for lymph node homing, int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
63
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(67 citation statements)
references
References 62 publications
4
63
0
Order By: Relevance
“…Related studies interrogating interactions between autoreactive Th17 cells and regulatory T cells activity in the context of experimental autoimmune encephalomyelitis (EAE) utilized a tandem calcium reporter with tdTomato and GCaMP6f to quantify the ratio between both cytoplasmic fluorophores. 38,39 In a related study, Kryatsous et al 40…”
Section: Tr Ack Ing Cellul Ar Inter Ac Ti On S During T Cell Priming ...mentioning
confidence: 96%
See 1 more Smart Citation
“…Related studies interrogating interactions between autoreactive Th17 cells and regulatory T cells activity in the context of experimental autoimmune encephalomyelitis (EAE) utilized a tandem calcium reporter with tdTomato and GCaMP6f to quantify the ratio between both cytoplasmic fluorophores. 38,39 In a related study, Kryatsous et al 40…”
Section: Tr Ack Ing Cellul Ar Inter Ac Ti On S During T Cell Priming ...mentioning
confidence: 96%
“…Immune cells will move in and out of the imaging plane and increase or decrease in signal intensity due to differences in tissue scattering and depth. Related studies interrogating interactions between autoreactive Th17 cells and regulatory T cells activity in the context of experimental autoimmune encephalomyelitis (EAE) utilized a tandem calcium reporter with tdTomato and GCaMP6f to quantify the ratio between both cytoplasmic fluorophores 38,39 . In a related study, Kryatsous et al 40 used the FRET‐based calcium sensor Twitch1 in combination with NFAT‐GFP to measure not only calcium signaling but also subsequently T cell activation by translocation of NFAT to the nucleus.…”
Section: Tracking Cellular Interactions During T Cell Priming In Lymp...mentioning
confidence: 99%
“…This is thought to occur as a result of both an intrinsic resistance of effector T-cells as well as suppression of regulatory T cell function by cytokines within the neuroinflammatory milleu (e.g., IL-6, IL-7, IL-18, IL-15, and TNF-α) (Walker, 2009). A recent study in EAE, found that Piezo1, a mechanosensitive ion channel known for its role in the inflammatory response to bacterial pathogens and cancer, may contribute to MS/EAE pathogenesis through selective repression of regulatory T cells (Jairaman et al, 2021). Accordingly, deletion of Piezo1 in regulatory T cells significantly attenuated EAE disease severity (Jairaman et al, 2021).…”
Section: T Lymphocytesmentioning
confidence: 99%
“…A recent study in EAE, found that Piezo1, a mechanosensitive ion channel known for its role in the inflammatory response to bacterial pathogens and cancer, may contribute to MS/EAE pathogenesis through selective repression of regulatory T cells (Jairaman et al, 2021). Accordingly, deletion of Piezo1 in regulatory T cells significantly attenuated EAE disease severity (Jairaman et al, 2021).…”
Section: T Lymphocytesmentioning
confidence: 99%
“…Piezo1 exerts significant regulatory effects on many kinds of immune cells. It has been reported that Piezo1 can regulate the functions of macrophages, DCs and T cells in inflammation and cancer (8,9,(24)(25)(26)(27). However, it is still unclear whether Piezo1-targeted DCs affect the differentiation of different subsets of T cells in cancer.…”
Section: Introductionmentioning
confidence: 99%